Middle Managers' Struggle Over Their Subject Position in Open Strategy Processes - Splitter, Violetta; Jarzabkowski, Paula; Seidl, David (Journal of Management Studies, 2023)
Abstract In this paper we examine middle managers’ struggle over their subject position as strategists in the context of participative strategy processes. Based on a longitudinal case study of a company undertaking an Open Strategy process, we show how the wider inclusion of front‐line employees in developing new strategy undermines the traditional subject position of middle managers. Based on these findings, we develop a process model depicting the recursive dynamics of middle managers’ struggles to maintain their subject positions in the face of employee participation. With these findings we contribute to the literature on middle managers by advancing our understanding of the implications of employee participation for middle managers’ subject position as strategists and their different ways of reclaiming their subject position. We also contribute to the literature on Open Strategy by revealing the implications for traditional strategy actors as well as by explaining the processual dynamics of participation over time.